The Effect of Product Quality and Product Innovation on Consumer Decisions Using Wood Packaging Material Services - Ramadani, Anisa Fitri; Nasution, Umar Hamdan; Rahim, Rani; Rangkuti, Sahnan; Nasution, Sarah (Ekonomis: Journal of Economics and Business, 2024)
This study aimed to determine the effect of product quality on consumer decisions using wood packaging material services at Carsurindo Siperkasa Medan to assess the impact of product innovation on consumer decisions using wood packaging material services at PT. Carsurindo Siperkasa Medan determines the effect of product quality and product innovation on consumer decisions to use wood packaging material services at PT. Carsurindo Siperkasa Medan. The analysis technique used in this study uses quantitative data analysis techniques, namely testing and analysing data. The respondents in the study were 45 people. From the results of this study, it was obtained the significance value of the product quality variable (X1) on the consumer purchasing decision variable (Y) based on the t-test was obtained at t count > t table (8.212) > (2.018), (Sig 0.001 < α0.05) thus H1 accepted and H0 is rejected, the conclusion: there is a significant effect of product quality (X1) on consumer purchasing decisions (Y). The significance value of the product innovation variable (X2) on the consumer purchasing decision variable (Y) based on the t-test obtained t count > t table (3.970) > (2.018), (Sig 0.001 <α0.05), thus H2 is accepted, and H0 is rejected, in conclusion. There is a significant influence of product innovation (X2) on consumer purchasing decisions (Y). Therefore the results of this study state that the two independent variables support the hypothesis. Based on the results of the F test, it was obtained that the F count > F table was (34.068 > 3.21), (Sig 0.001 <α0.05); thus, H3 was accepted, and H0 was rejected. The conclusion: Product quality and innovation have a significant effect on consumer purchasing decisions. It shows that if the company can improve product quality and innovation, consumers will be interested in buying these products, increasing consumer purchasing decisions.